Climate Change Adaptation in Latin America Managing Vulnerability, Fostering Resilience (Climate Change Management,, 2018)
This book showcases experiences from research, field projects and best practice in climate change adaptation in countries in the Latin American region, focusing on managing vulnerability and fostering resilience. It includes a selection of papers presented at a specialist symposium on climate change adaptation held in Rio de Janeiro, Brazil in November 2016. Consistent with the need for more cross-sectoral interaction among the various stakeholders working in the field of climate change adaptation in Latin America, the book documents and disseminates the wealth of experiences in the region. It is divided into two main parts: Part 1 addresses the current and future impacts of climate change on fauna, flora and landscapes, while Part 2 is concerned with the socio-economic aspects of climate change adaptation, analyzing some of the main problems prevailing in this vulnerable region and examining ways to address them.